This would make a good story someday - Levy, Dana Alison (Delacorte Press, 2017)
Although not thrilled when her summer plans are upended for a surprise cross-country train trip with her family and embarrassed because one of her moms is writing a tell-all book about the trip, twelve-year-old Sara Johnston-Fischer finds herself changing along with the landscape outside the train windows.